Al-Jahiz in praise of books - Montgomery, James E. (Edinburgh studies in classical Arabic literature, 2013)
Al-Jahiz was a bibliomaniac, theologian, and spokesman for the political and cultural elite, a writer who lived, counselled and wrote in Iraq during the first century of the 'Abbasid caliphate. 'In Praise of Books' explores the centrality of books to Al-Jahiz's work and to the society he lived in.